Frequency-Regulatable Electric Drive of Pumping Installations (Eurasian Scientific Herald, 2022)
The article presents a methodology for a feasibility study of the use of a frequency-controlled electric drive in pumping units. A method for calculating the use of a frequency-controlled electric drive in pumping units is given and it is proved that the application makes it possible to use large pumping units in the low flow mode and, therefore, reduce their total number. The problem of determining the technical and economic indicators of pumps of the D series is also considered and it is shown that the linear dimensions of pumping units grow much more slowly than their power and flow. An expression was cited for determining the relative linear dimensions of the compared aggregates